2021
DOI: 10.1017/s1368980021004559
|View full text |Cite
|
Sign up to set email alerts
|

Trends and determinants of minimum dietary diversity among children aged 6–23 months: a pooled analysis of Indonesia Demographic and Health Surveys from 2007 to 2017

Abstract: Objective: To examine minimum dietary diversity (MDD) trends and determinants among children aged 6–23 months. Design: Secondary analysis of the Indonesia Demographic and Health Surveys (IDHS) between 2007 and 2017. The primary outcome was MDD, the consumption of at least five out of eight food groups (MDD-8). We included a total of 5015 (IDHS 2007), 5050 (IDHS 2007) and 4925 (IDHS 2017) children aged 6 to 23 months to estimate trends of MDD-8 and to identify factors associated with MDD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 31 publications
12
24
0
1
Order By: Relevance
“…This is in line with the research conducted in India (77%) (19) and Myanmar (75.4%) (46). But our study indicated that this percentage is higher than studies conducted in Bangladesh (58.1%) (47), Nepal (53.5%) (17), Indonesia (46.7%) (20), Sri Lanka (29%) (21), and a study in two South-East Asian countries, namely, Cambodia (52.3%) and Indonesia (41.8%) (46), which shows that children aged 6-23 months have inadequate access to MDD. The discrepancy might be due to differences in food cultures (10,27,46).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the research conducted in India (77%) (19) and Myanmar (75.4%) (46). But our study indicated that this percentage is higher than studies conducted in Bangladesh (58.1%) (47), Nepal (53.5%) (17), Indonesia (46.7%) (20), Sri Lanka (29%) (21), and a study in two South-East Asian countries, namely, Cambodia (52.3%) and Indonesia (41.8%) (46), which shows that children aged 6-23 months have inadequate access to MDD. The discrepancy might be due to differences in food cultures (10,27,46).…”
Section: Discussionsupporting
confidence: 91%
“…In many countries, less than one-quarter of children are reported not getting the nutrition they need to grow well, particularly in the crucial first 1,000 days (13,16). The magnitude of inadequate minimum dietary diversity (MDD) in Nepal was 53.5% (17); in India, it ranges from 36.15 to 77% (18,19), MDD in Indonesia was 46.7% (20), and MDD in Sri Lanka was 29% (21).…”
Section: Introductionmentioning
confidence: 99%
“…We selected the contributory factors to socioeconomic inequality in dietary diversity based on our study on MDD determinants in Indonesia. For the present study analysis, we only included significant variables in relation to MDD found in our previous research [ 23 ]. These variables included child’s age (6–11 months, 12–17 months, 18–23 months), mother’s education (none or incomplete primary school, completed primary school, completed secondary school, completed higher education), mother’s access to media (none, at least one media), mother’s occupation (not working, agricultural, non-agricultural), father’s occupation (not working, agricultural, non-agricultural), number of ANC visits in the last pregnancy (<4 visits, ≥4 visits), household wealth (poorest, poorer, middle, richer, richest), area of residence (rural, urban), and regions (Java and Bali, Sumatera, Kalimantan, Sulawesi, Eastern Indonesia).…”
Section: Methodsmentioning
confidence: 99%
“…Children of higher economic status are at greater odds of receiving foods from diverse foods [ 19–23 ]. Mothers with higher education are more likely to have children who consume a more varied diet than those with lower education [ 19–21 , 23–25 ]. Other factors, such as maternal employment [ 26 ], paternal education [ 20 , 27 ], antenatal care (ANC) [ 20 , 25 ] and residency [ 21 , 26 ], are often related to increasing dietary diversity but have shown mixed results across studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation